THE INFLUENCE OF FIRM SIZE AND PROFITABILITY ON FIRM VALUE WITH PROFIT GROWTH AS A MEDIATION: Empirical Study of Food and Beverage Subsector Companies Listed on the Indonesian Stock Exchange in the 2017-2021 Period - Abdul Azis Solehuddin; Fauji Sanusi; Suryani, Emma (Management Science Research Journal, 2023)
This study investigates the impact of firm size and profitability on firm value, with revenue growth acting as a mediator between the two. This study uses quantitative methods to test comparative causality. The data used is secondary data from the financial statements of each company obtained from both the company's official website and the IDX. The sampling of this study used non-probability purposive sampling techniques in food and beverage sector companies listed on the IDX for the 2017-2021 period with complete financial data. The research data is panel data and is analyzed using Eviews 12 with the following levels of analysis: descriptive statistics, regression model estimation, classical assumptions, and panel data regression to path analysis. The analysis results show that firm size and profitability have a significant positive effect on earnings growth, firm size and earnings growth can significantly increase firm value, profitability cannot increase firm value, and earnings growth cannot mediate the effect of firm size, but can mediate the effect of firm size. mediate the effect of profitability on firm value.